Influence of melt superheat treatment on corrosion resistance of Gd-based BMG in 3.5% NaCl solution. (15th June 2016) - Zhang, Xiaorong; Guo, Jing; Liu, Haipeng; Song, Yuepeng; Xu, Lingfeng; Liu, Jingtao
Abstract: Gd55 Al25 Cu10 Co10 bulk metallic glass (BMG) was prepared by copper mold blow casting method with different superheat temperatures. Polarization tests, electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) measurements were used to study the influence of superheat treatment on corrosion resistance of Gd55 Al25 Cu10 Co10 in 3.5% NaCl solution at room temperature. The potentiodynamic polarization analysis shows that the corrosion resistance ability of Gd-based BMG after superheat treatment at different superheat temperatures ranks: 1105 °C > 1214 °C > 1066 °C > 919 °C, which agrees well with that of EIS data. In addition, the SEM results reveal that the corrosion products gradually become more uniform for Gd-based BMG at higher superheat temperature and exhibits the best at 1105 °C. Also, it is interesting that there exists no corrosion pits for all Gd-based BMG. The EDS and XPS results reveal that corrosion resistance has a positive relation with highly corrosion-resistance oxides of corrosion products. It is also found that corrosion resistance ability is in accordance with glass-forming ability (GFA). All these results are considered to be related to the uniform and homogeneous microstructure after superheat treatment Graphical abstract: Highlights: Gd-based bulk metallic glass prepared at higher superheat temperature gradually shows better corrosion resistance and reaches the best at 1105 °C. No pitting corrosion occurs in 3.5% NaCl solution for all Gd-based bulk metallic glass. Superheat treatment could be a method to improve corrosion resistance of metallic glass.